Development of electrooptic devices by strengthening electromagnetic fields using colloidal silver solutions. (April 2020) - Sugito, H; Khumaeni, A; Firdausi, K S; Azam, M
Abstract: The development of electrooptic devices by strengthening the electromagnetic fields using colloidal silver has been carried out. This tool works based on the electrooptics method. The samples used were aquabides and a solution of aquabides mixed with colloidal silver with various concentrations. The light source used is a green laser with a wavelength of 532 ± 10 nm. Measurements are made by observing changes in the natural polarization angle and the electro-optical polarization angle. The test results show that at a concentration of 0-0.25 there is a significant change in the polarization angle to the increase in the external electric field (0-9 kV). While at a concentration of 2.5-1 there is a tendency that there is no change in the polarization angle.